Bargaining power and equilibrium consumption - Gersbach, Hans; Haller, Hans (CESifo working papers, 2005)
We examine how a shift of bargaining power within households operating in a competitive market environment affects equilibrium allocation and welfare. If price effects are sufficiently small, then typically an individual benefits from an increase of bargaining power, necessarily to the detriment of others. If price effects are drastic the welfare of all household members moves in the same direction when bargaining power shifts, at the expense (or for the benefit) of outside consumers. Typically a shift of bargaining power within a set of households also impacts upon other households. We show that each individual of a sociological group tends to benefit if he can increase his bargaining power, but suffers if others in his group do the same.